The Impact Of Public Policy On Social Welfare: An Analysis Of Social Assistance Programs in The Digital Era - Muhammad Natsir Mallawi (International Forum of Researchers and Lecturers, 2025)
This study investigates the impact of public policy on social welfare, specifically through the lens of social assistance programs in the digital era. As technology continues to evolve, the implementation of social assistance programs has transformed, leading to new opportunities for enhancing service delivery and accessibility. This research employs a mixed-methods approach, combining quantitative data analysis with qualitative case studies to assess the effectiveness of these programs in improving social welfare outcomes. The findings reveal that while digital tools can enhance the reach and efficiency of social assistance initiatives, challenges such as digital divide and data privacy concerns must be addressed to ensure equitable access for all beneficiaries. Ultimately, this study underscores the importance of integrating technology into public policy frameworks to foster sustainable social welfare improvements in an increasingly digital world.